2018
DOI: 10.1242/jeb.187351
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to intense turbulence induces a sustained life-history shift in echinoids

Abstract: In coastal ecosystems, attributes of fluid motion can prompt animal larvae to rise or sink in the water column and to select microhabitats within which they attach and commit to a benthic existence. In echinoid (sea urchin and sand dollar) larvae living along waveexposed shorelines, intense turbulence characteristic of surf zones can cause individuals to undergo an abrupt life-history shift characterized by precocious entry into competencethe stage at which larvae will settle and complete metamorphosis in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…For example, oyster larvae stop swimming and sink in response to the turbulent layer near the substrate (ca 1 cm from the surface) [278]. In some echinoderm larvae, turbulence may induce competence to settle [273,337,338].…”
Section: (B) Flow-based Settlementmentioning
confidence: 99%
“…For example, oyster larvae stop swimming and sink in response to the turbulent layer near the substrate (ca 1 cm from the surface) [278]. In some echinoderm larvae, turbulence may induce competence to settle [273,337,338].…”
Section: (B) Flow-based Settlementmentioning
confidence: 99%
“…The size of the sand dollars was another favorable factor for their use as an indicator of the hydrological dynamics of Praia de Santos. Figure 4 shows a predominance of adult animals, with higher chances of reproducing before being released to the supra coast and dying [29][30][31][32][33][34] found that water turbulence induces behavioral responses to the transition of Pacific sand dollar larvae (Dendraster excentricus) from the planktonic to the benthic phase. This same phenomenon may not occur with the larvae of Melitta quinquesperforata, seen by the absence of younger individuals (below 4cm) that possibly occupy places distant from the surf zone of Santos beach.…”
Section: Discussionmentioning
confidence: 99%